Labdane Diterpenoids from Salvia leriifolia: Absolute Configuration, Antimicrobial and Cytotoxic Activities - Farimani, Mahdi Moridi; Taleghani, Akram; Aliabadi, Abbas; Aliahmadi, Atousa; Esmaeili, Mohammad Ali; Namazi Sarvestani, Nazanin; Khavasi, Hamid Reza; Smieško, Martin; Hamburger, Matthias; Nejad Ebrahimi, Samad (Planta Medica, 2016)
Fractionation of an n-hexane extract of the aerial parts of Salvia leriifolia led to the isolation of two new (1, 2) and two known (3, 4) labdane diterpenoids, together with three other known compounds. The structures were established by a combination of 1D and 2D NMR, and HRESIMS. The structures of 1 and 3 were confirmed by single-crystal X-ray analysis. The absolute configuration of 1–4 was established by electronic circular dichroism spectroscopy. Compounds 1–4 were evaluated for their cytotoxic activities against MCF-7 human breast cancer cells. Labdanes 3 and 4 were additionally tested against MDA-MB231 human breast cancer and DU-145 human prostate cancer cell lines. Compound 4 showed IC50 values of 25, 50, and 50 µM against MCF-7, MDA-MB231, and DU-145 cells, respectively. Compounds 1–4 were tested for activity against gram-positive (Staphylococcus aureus) and gram-negative (Escherichia coli) bacteria. Compound 3 showed an MIC of 213 µM against methicillin-resistant S. aureus.
Keywords: Salvia leriifolia; Lamiaceae; diterpene; absolute configuration; antibacterial activity; cytotoxicity